The nature of occupational health services for employees in selected public health facilities in Gauteng province, South Africa. - Pretorius, Kim (My University, 2017)
Background: Literature suggests that, internationally and nationally, insufficient priority is given to Occupational Health and Safety (OHS) for healthcare workers in public health institutions. This is accompanied by a generalised lack of clear accountability for OHS. Anecdotal evidence on OHS in public healthcare institutions in the Republic of South Africa (RSA) suggests this is no different, with the bare minimum of services being offered in most facilities. Few studies have been completed in on this subject in RSA. If the status of Occupational Health service provision is unknown, there will continue to be a lack of prioritisation of OHS, and minimal accountability for poor performance with the continued neglect of the healthcare worker in these institutions. Purpose and objectives: The purpose of this research study was to explore and describe the nature, range and extent of occupational health services (OHS) offered to employees in selected public health facilities in Gauteng, and to assess the extent to which the services meet the National Department of Health (NDoH) Guidelines for an Occupational Health Services in the Healthcare Setting. The overall objectives of the study were to explore and describe the nature, range and extent of OH services at the public hospitals and CHCs as regards the level of compliance with the nine recommended components of an occupational health service, as described in the NDoH Guidelines, and to explore and describe opportunities and constraints in the delivery of a comprehensive OH service as described in the NDoH Guidelines. Research methodology: The research design utilized for this study was a cross sectional, exploratory and descriptive study, using a researcher-administered, semi-structured questionnaire, which was used as a guide for an interview process. The method of analysis chosen for the current study was Mayring’s Content Analysis, which makes provision for the inclusion of quantitative and qualitative factors. Findings: The overall outcomes of the research indicated that compliance to all nine components of the NDoH guideline was poor among all hospitals and CHCs in the study. The constraints and opportunities were discussed, with overriding findings being problems with a lack of OHS policy and guidelines, lack of budget for OH, inadequate management of OH services, lack of education and dissemination of required knowledge, poor governance and strategic planning, lack of qualified personnel and a general disinterest in OH from the top health authority down to facility level. The hospitals were more compliant and enjoyed a wider range of services than the CHCs. Conclusions: The information obtained from the findings show that all aspects of OHS for healthcare workers in the public health facilities in this study are neglected. The findings may be used to improve organisational policies and practices to address and improve the occupational health and safety services offered to employees in the high risk public healthcare institutions.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree: Master of Science in Nursing (Occupational Health Nursing),2017
Keywords: Occupational health services; Occupational therapy